How Work–Family Conflict and Work–Family Facilitation Affect Employee Innovation: A Moderated Mediation Model of Emotions and Work Flexibility - Wang, Zhicheng; Qiu, Xingyu; Jin, Yixing; Zhang, Xinyan (Frontiers in Psychology, 2022)
This paper aims to verify the effect of work-family conflict and work-family facilitation on employee innovation in the Digital Era. Based on the resource conservation theory, this study regards the work-family relationship as a kind of conditional resource. Employees who are in a state of lack of resources caused by work-family conflict will avoid consuming further resources to perform innovation activities in order to maintain existing resources; Employees who are in a state of sufficient resources, are more willing to invest in existing resources to obtain more resources. In this study, 405 employees from enterprises in the provinces of Jiangsu, Anhui, Sichuan, and Guangdong, and in Tianjin of China were selected as the research object，These companies are knowledge-based companies, and their employees frequently transfer knowledge at work. From the employee level, we collected questionnaires from the front-line employees of these companies. The results show that negative and positive emotions mediate the effect of work-family conflict and work-family facilitation on employee innovation. Moreover, work flexibility has a significant moderating effect on the mediating role between work-family facilitation and employee innovation behavior. In the Digital Era, when facing different work-family situations, employees need to pay attention to, and dredge, their negative emotions to avoid their reducing innovative behaviors due to self-abandonment; in parallel, they need to guide their positive emotions toward innovation, so as to promote their innovative consciousness and behavior. This paper expands the research perspective of employee innovation behavior.